Efektifitas Teori Belajar Perspektif Psikologi Fungsionalisme pada Anak Usia 12 sampai 17 Tahun - Inayah, Eka Salma; YS, Arba’iyah; Almasih, Imroatul Asheila; Wulandari, Jesika (MASALIQ, 2023)
In psychology, there are many learning theories from various schools that exist. As one of them is the learning theory of functionalism perspective. Self-learning theory is here to help us as teachers in conducting classroom learning. Not only for teachers, learning theory also plays a role in the formation of the character of each student. So we did this research to find out the effectiveness of learning theory in the perspective of functionalism psychology in the education of children aged 12-17 years. Because the suitability of the learning theory used by students will likely be one of the determinants of the results of how their education will be in the future.